Evaluation of the physicochemical and sensory characteristics of ripening mandarins - MICARONI, Isabela Rótoli; MEDEIROS, Simone Daniela Sartorio de; SCHINOR, Evandro Henrique; VERRUMA-BERNARDI, Marta Regina; DEVITE, Fernando Trevizan; GONÇALES Thaís Lugli; BASTIANEL Marinês (Food Science and Technology, 2023)
The provision and expansion of the number of mandarin varieties and hybrids are of great importance for the market of fresh fruit, as Brazilian commercial orchards are based on a small number of varieties, which contributes to cultural vulnerability. The aim of this study was to verify, by univariate analyses, the possible physicochemical and sensory differences of early mandarin varieties: Ponkan IAC172, Múscia IAC607, Span IAC595, and the hybrid TP×TM11 (Ponkan IAC172×Murcott IAC221). The variety Span IAC595 presented expressive physicochemical characteristics, besides presenting sensory characteristics compatible with consumer preferences and a relation superior to the other varieties studied. The hybrid TM×TP11 obtained the lowest preference, demonstrating that attributes such as ease of peeling, skin color, and size are important in consumer’s choice, indicating an importance of the studied attributes for the preference of a mandarin, that must be considered in the production of new varieties for the fresh fruit market.